Promoting Moderate-Vigorous Physical Activity in Overweight Minority Girls - Norma Olvera; Marilynn Graham; Jessica McLeod; Stephanie F. Kellam; Nancy F. Butte (International Journal of Pediatrics)
There is limited research on the types of activities that are most effective for promoting MVPA in children. Purpose. To assess which types of activities elicit MVPA in overweight minority girls. Methods. Sample consisted of 31 overweight (BMI≥85th percentile) Latina and African-American girls (mean age 10.3±1.2 years). Participants wore an Actical accelerometer each day for 8 hours for 15 days to assess engagement in MVPA during their participation in a three-week activity intervention that included traditional fitness, sport skills, games, dancing, and flexibility sessions. Results. On average 62% of participants met the MVPA recommended guidelines (60 min/5d/wk) with an average of 68.5±14 minutes of MVPA across the three weeks. Traditional fitness sessions elicited the highest percent of MVPA (mean time spent in MVPA=32%), followed by dancing and games (mean time spent in MVPA=21%), sports skills (mean time spent in MVPA=18%), and flexibility (mean time spent in MVPA=7%). Step aerobics and rumba fitness elicited the highest proportions of MVPA. Conclusion. Traditional fitness activities were identified as the most successful in eliciting MVPA in overweight Latina and African American girls.